131I-mIBG Therapy in the Management of High-Risk Neuroblastoma: A Retrospective Study from a Tertiary Level Hospital in South India - A.R. Vishnu; Saumya Sunny; Julie Hephzibah; Leni G. Mathew; Rikki Rorima John (Indian Journal of Medical and Paediatric Oncology)
Introduction Neuroblastoma is the most common extracranial solid tumor in childhood. The data on the treatment experience with 131iodine-meta-iodo-benzyl-guanidine (131I-mIBG) and clinical outcome data are meager from India.